Comparing the efficacy and safety of low, medium, and high dosages of selexipag for treating pulmonary hypertension: A systematic review and meta‐analysis - Shang Wang; Yi Yan; Jian Zhang; Ping Yuan; Ci‐Jun Luo; Hong‐Ling Qiu; Hui‐Ting Li; Jian Xu; Lan Wang; Tian‐Lan Li; Rong Jiang (Animal Models and Experimental Medicine, 2024)
Abstract Background The maintenance dosage of selexipag is categorized as low, medium or high. In order to assess the efficacy and safety of different dosages of selexipag for the risk stratification of pulmonary arterial hypertension (PAH), we performed a systematic review and meta‐analysis. Methods Studies assessing PAH risk stratification indices, such as the World Health Organization functional class (WHO‐FC), six‐minute walk distance (6MWD), N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) level, right atrial pressure (RAP), cardiac index (CI) and mixed venous oxygen saturation (SvO2), were included. Results Thirteen studies were included. Selexipag led to improvements in the 6MWD (MD: 24.20 m, 95% CI: 10.74–37.67), NT‐proBNP (SMD: −0.41, 95% CI: −0.79–0.04), CI (MD: 0.47 L/min/m2, 95% CI: 0.17–0.77) and WHO‐FC (OR: 0.564, 95% CI: 0.457–0.697). Subgroup analysis demonstrated that all three dosages improved the 6MWD. A moderate dosage led to improvements in the CI (MD: 0.30 L/min/m2, 95% CI: 0.15–0.46) and WHO‐FC (OR: 0.589, 95% CI: 0.376–0.922). Within 6 months of treatment, only the WHO‐FC and CI were significantly improved (OR: 0.614, 95% CI: 0.380–0.993; MD: 0.30 L/min/m2, 95% CI: 0.16–0.45, respectively). More than 6 months of treatment significantly improved the 6MWD, WHO‐FC and NT‐proBNP (MD: 40.87 m, 95% CI: 10.97–70.77; OR: 0.557, 95% CI: 0.440–0.705; SMD: −0.61, 95% CI: −1.17–0.05, respectively). Conclusions Low, medium, and high dosages of selexipag all exhibited good effects. When treatment lasted for more than 6 months, selexipag exerted obvious effects, even in the low‐dosage group. This finding is important for guiding individualized treatments.